The middle domain of Hsp104 can ensure substrates are functional after processing. - Hannah E Buchholz; Jane E Dorweiler; Sam Guereca; Brett T Wisniewski; James Shorter; Anita L Manogaran (PLoS Genetics)
Molecular chaperones play a central role in protein disaggregation. However, the molecular determinants that regulate this process are poorly understood. Hsp104 is an AAA+ ATPase that disassembles stress granules and amyloids in yeast through collaboration with Hsp70 and Hsp40. In vitro studies show that Hsp104 processes different types of protein aggregates by partially translocating or threading polypeptides through the central pore of the hexamer. However, it is unclear how Hsp104 processing influences client protein function in vivo. The middle domain (MD) of Hsp104 regulates ATPase activity and interactions with Hsp70. Here, we tested how MD variants, Hsp104A503S and Hsp104A503V, process different protein aggregates. We establish that engineered MD variants fail to resolve stress granules but retain prion fragmentation activity required for prion propagation. Using the Sup35 prion protein, our in vitro and in vivo data indicate that the MD variants can disassemble Sup35 aggregates, but the disaggregated protein has reduced GTPase and translation termination activity. These results suggest that the middle domain can play a role in sensing certain substrates and plays an essential role in ensuring the processed protein is functional.